Hypoxia-Enhanced N2O Production Under Ocean Acidification in the Bohai Sea - Gu, Ting; Jia, Dai; Ma, Xing; Peng, Liying; Zhang, Guicheng; Wei, Yuqiu; Lou, Tingting; Sun, Jun (Frontiers in Marine Science, 2021)
N2O is progressively known as a powerful greenhouse gas and can contribute to the exhaustion of the ozone sphere. Hypoxia and ocean acidification are becoming more intense as a result of climate change. Hypoxia stimulates N2O emissions, while acidification tends to have different effects on N2O emissions in different oceans. Hypoxia and ocean acidification may play a critical role in the evolution of future oceanic nitrous oxide emissions, including air-sea fluxes. However, the interactive effects of hypoxia and ocean acidification to N2O emissions remain uncertain. The occurrence of ocean acidification in the seasonal oxygen minimum zone of the Bohai sea has also been demonstrated during our cruises. We conducted laboratory incubation experiments to examine the effects of ocean acidification and hypoxia on N2O emissions in Bohai Bay. With ocean acidification, the contributions to N2O emissions were negative, while hypoxia contribute positive impact. And the results of incubation experiments demonstrated that the coupling of ocean acidification and hypoxia significantly increased the N2O emission, but the increase was between the effects of the two treatments alone, there is an antagonistic relationship between ocean acidification and hypoxia. Through the SEM analysis, the total effects of hypoxia treatment on N2O emission changes weakened such effects of ocean acidification treatment, the total effects were positive. Generally speaking, our results suggested that the N2O emission from coastal water of Bohai sea may increase under future climate change scenarios due to increasingly serious problem of both ocean acidification and hypoxia.